Using acute hypervolaemic haemodilution as blood conservation technique in a Jehovah’s witness patient undergoing an emergency transphenoidal surgery: a Sabah experience - Yeap, Boon Tat; Teah, Ming Kai; Zenian Sofan (BMJ Publishing Group Limited, 2021)
Jehovah’s Witnesses (JW) is a branch of Christianity which was founded in 1872. However, their beliefs differ from other Christians in many ways. Majority of JW believe that it is against the teaching of God should they receive blood transfusion, while minority think receiving own blood or others is acceptable. These vast beliefs should always be respected by all medical practitioners to avoid medicolegal implications. The differing beliefs about blood transfusion is certainly a huge challenge to the surgeons and anesthesiologists, especially dealing with major surgeries. Thus, effective surgical and anaesthetic techniques are focused to minimise blood loss to avoid unnecessary blood transfusion. We report a JW patient who successfully underwent an emergency endoscopic transsphenoidal surgery secondary to pituitary apoplexy; highlighting our intraoperative acute hypervolaemic haemodilution technique to reduce blood loss.